'London particular': the city, its atmosphere and the visibility of its objects. Issue 8 (16th November 2016) - Hyde, Timothy
Abstract : Over the course of the nineteenth century, the smoke-filled atmospheres of London and other industrial cities were the subject of aesthetic, scientific and legal inquiry. Reconstructing the conjunction of such inquiries in a pivotal architectural episode—the rebuilding of the Houses of Parliament—reveals an important transformation in the understanding of the relationship between a city and its architectural objects. Where it once seemed possible to regard these objects (and their architects) as independent, discrete participants in the larger material and administrative domains of the city, the expanding knowledge and judgements of the atmosphere and its effects produced an entirely different perception. The city and its architectural objects were co-extensive, involuntary participants in an encompassing process of change registered by two newly recognised categories: decay and maintenance.